Pengaruh Kompetensi Pedagogik Guru Terhadap Minat Belajar Bahasa Arab - Nurul Hijrah; Amran AR; Ramli (IAI Muhammadiyah Sinjai, 2022)
This study aims to determine the effect of teacher pedagogical competence on interest in learning Arabic in class VIII MTsN 1 Sinjai. The type of research used in this research is ex post facto using a quantitative approach. The object of this research is 75 students of class VIII, with a total sample of 59 people, the results of this study indicate that there is an influence between the teacher's pedagogic competence and interest in learning Arabic for class VIII students of MTsN 1 Sinjai. based on the results of simple linear regression analysis, the value obtained if t-count < t-table, then H0 is accepted. Ha is rejected, if t-count > t-table, then Ha is accepted, and H0 is rejected. Based on the coefficients table the t-count (3.852) > t-table (1.672). So it can be interpreted that the teacher pedagogic competence variable (X) affects the learning interest variable (Y).